2019
DOI: 10.1007/s11661-019-05415-6
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of Bainite Transformation and Simultaneous Carbon Enrichment in Austenite in Low-Alloyed TRIP Steel Using Time-of-Flight Neutron Diffraction Techniques

Abstract: An in situ neutron diffraction experiment during austempering of low-alloyed transformationinduced plasticity steel, Fe-1.48Si-1.52Mn-0.15C, in wt pct was conducted. In this study, timeof-flight neutron diffractometer with a large detector coverage, iMATERIA at J-PARC MLF, was employed. The phase fraction and carbon concentration in austenite could be quantitatively determined with a time resolution 1 minute although considerable textures existed for both ferrite and austenite. The carbon concentration in aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…Note that, in our earlier work ( [24] and more recently also [46]), we showed that different enrichment of austenite with C during the ausferrite transformation process is visible in asymmetries of the (111) reflection. This peak asymmetry could be described with two separate peaks.…”
Section: Comparison Of Neutron Diffraction To Dilatometrysupporting
confidence: 59%
“…Note that, in our earlier work ( [24] and more recently also [46]), we showed that different enrichment of austenite with C during the ausferrite transformation process is visible in asymmetries of the (111) reflection. This peak asymmetry could be described with two separate peaks.…”
Section: Comparison Of Neutron Diffraction To Dilatometrysupporting
confidence: 59%
“…An earlier report describes the detail furnace and instrument set‐up for in situ neutron experiments. [ 37 ] A heat cycle for the present in situ experiments includes holding at room temperature for 10–15 min, heating from room temperature to 670 and 1240 K for the as‐built and after HPT specimens, respectively, at a heat ramping rate of 4 K min −1 , holding the targeted maximum temperatures for 10 min, and subsequent fast furnace cooling towards room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The RA phase leading to the transformation‐induced plasticity (TRIP) effect in these advanced multiphase steels contributes to the improved tensile ductility with a concomitant increase in tensile strength. [ 4–7 ]…”
Section: Introductionmentioning
confidence: 99%
“…The RA phase leading to the transformation-induced plasticity (TRIP) effect in these advanced multiphase steels contributes to the improved tensile ductility with a concomitant increase in tensile strength. [4][5][6][7] The latest development of ultrahigh strength steels has adapted to the new concept of microstructural design involving multiphase, and multiscale microconstituents. [8][9][10] In the past decade, a few novel heat treatment processes, such as quenching and partitioning (Q&P), [11][12][13] quenching-partitioning-tempering (Q-P-T), [14] and lowtemperature bainitic transformation (close to or even below M s temperature), [15][16][17] have been designed to achieve an excellent combination of high/ultrahigh strength combined with good low temperature toughness and reasonable ductility.…”
mentioning
confidence: 99%